2015
DOI: 10.1117/1.oe.54.8.081208
|View full text |Cite
|
Sign up to set email alerts
|

Photoelastic materials and methods for tissue biomechanics applications

Abstract: Abstract. Digital photoelasticity offers enormous potential for the validation of computational models of biomedical soft tissue applications. The challenges of creating suitable birefringent surrogate materials are outlined. The recent progress made in the development of photoelastic materials and full-field, quantitative methods for biomechanics applications is illustrated with two complementary case studies: needle insertion and shaken baby syndrome. Initial experiments are described and the future exciting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…Here, we utilize birefringence in the solid. Gelatin as our tissue phantom becomes doubly refractive under stress and is then suitable for photoelastic photography 16 . Those two refracted rays possess directions of polarization coinciding with the local principal stress directions.…”
mentioning
confidence: 99%
“…Here, we utilize birefringence in the solid. Gelatin as our tissue phantom becomes doubly refractive under stress and is then suitable for photoelastic photography 16 . Those two refracted rays possess directions of polarization coinciding with the local principal stress directions.…”
mentioning
confidence: 99%
“…A recent report described the difficulty in finding a suitabl punctured with a needle [3]. Figure 1 displays the differences between the tissue clinging and tissue tearing.…”
Section: Materials Requirementsmentioning
confidence: 99%
“…Konjac glucomannan I thickening agent to make transparent jellies. A recent report showed that when a needle punctures konjac gel it produces a different puncture crack than conventional gels [3]; it does not tear and resists crack formation. The following section describes the development of konjac jelly as a suitable skin tissue surrogate.…”
Section: Materials Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to puncture is another aspect of soft tissue surrogate investigations. Tomlinson and Taylor [10] have examined the feasibility of photoelasticity to visualize and quantify stresses due to needle insertion into different soft tissue surrogates. Some investigators have contrasted rounded probes relative to sharp medical needles for studying the puncture resistance [11].…”
Section: Introductionmentioning
confidence: 99%